[Address, to welcome Sir Edmund Barton, Ottawa] - Barton, Edmund, Sir, 1849-1920. (1902)
Address by the citizens of the capital of the Dominion of Canada who welcome the first Prime Minister of the Federated Commonwealth of Australia to Ottawa.
Manuscript reference no.: NLA MS 1612.
Keywords: Barton, Edmund, -- Sir, -- 1849-1920.; Prime ministers -- Australia; Visits of state -- Canada; Australia -- Foreign relations -- Canada; Canada -- Foreign relations -- Australia; Federal politicians